Kepemimpinan Pendidikan dalam Al-Qur’an - Isna Nurul Inayati (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
Problems related to moral decadence, industrialization of education and the crisis of leadership is one of the problems that must be faced by the community in the current era of globalization. To face this challenge, the institution appears to be necessary to increase the quality towards better. Efforts to improve the quality of education will not be detached from the role of educational leaders who in this case is the head of school as top figures who